Dental Treatment of a Patient with Treacher Collins Syndrome Under General Anaesthesia: A Case Report - Aslı Soğukpınar; Merve Erkmen Almaz (Cumhuriyet University, 2019)
This article reports a case of Treacher Collins syndrome (TCS) in a five-year-old male patient treated in Kırıkkale University, Department of Pediatric Dentistry. We defined the clinic signs and symptoms of the case and suggested a treatment plan. Treatment procedures for malformations caused by the syndrome should be planned and performed specifically for the patient. In our patient with low treatment compliance, dental examination, filling and partial prosthesis treatment was successfully applied under general anesthesia.